Aplicação do método das bielas para o dimensionamento de consolos curtos com suporte da otimização topológica - Cedrim, Matheus Barbosa Moreira (2019)
Reinforced concrete short corbels are components of connections between precast elements, characterized to represent typical conditions of geometrical and static discontinuity. For its design, in general, it is not assumed the classical theory of flexure, because the assumptions of the plane sections remain plane after the deformation are not valid. With the strut and tie method, a model of a self-balanced truss, composed by struts, nodal zones and ties, it comes a strategy of representation of the principal stresses flow in a linear elastic behavior in these components. In the literature, several models are proposed by the design codes and researchers as the proper representation of corbels’ strength model. Motivated by the fact that there is no unique solution to obtain the strut and tie model, topology optimization is an indicated technique to the definition of a methodology of conception of these models. Using a numerical analysis in finite elements, the formulation of SIMP (Solid Isotropic Material with Penalization) method of topology optimization is defined with the criterion of minimum strain energy restricted by the volumetric fraction. In the design of short corbels, analyzing different geometries and boundary conditions, a comparative analysis of the trusses models was carried out, checking that models obtained using topology optimization can be consistent with the design codes, as long as performance requirements and stresses limits are respected. Thus, it is shown that topology optimization is an effectual tool to the conception of preliminary models, it should always be ensured the fundamentals of strut and tie method.